Genetic Association and Expression of JHDM1A Gene Related to Meat pH in Commercial Pigs - A. Kayan; S. Theerawatanasirikul; P. Lekcharoensuk; C. Boonkaewwan; A. Kaewkot; M. Chanaksorn; C. Tantikositruj; A. Gunawan (Faculty of Animal Science, Bogor Agricultural University, 2022)
An experiment was conducted to study the association and expression of JHDM1A gene as a candidate gene for meat quality. The polymorphism was genotyped by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using restriction enzyme on a total of 300 muscle samples of [Duroc × (Large White × Landrace)] pigs. Results showed that JHDM1A gene was significantly associated with meat pH 45 min post-mortem (p.m.) (p<0.05). Allele frequencies for G and C were 0.53 and 0.47. The genotype frequencies for GG, GC, and CC were 0.24, 0.58, and 0.18, respectively. The Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) study were analyzed between low and high pH 45 min p.m. groups (n=10 per group) according to the association result. JHDM1A expression was higher in animals with a low post-mortem meat pH 45 min (p<0.05). Therefore, polymorphism and expression in the porcine JHDM1A gene might be the important candidate genes to improve meat quality traits in terms of meat pH.